THE IMPACT OF TELEHEALTH ON PSYCHOSOCIAL WELL-BEING AND PATIENT SATISFACTION DURING PREGNANCY: A LITERATURE REVIEW - Ira Nurwahyu Kusuma; Farida Fitriana (Indonesian Midwifery and Health Sciences Journal)
Background: Telehealth has rapidly evolved as a critical tool in healthcare, particularly during the COVID-19 pandemic, enhancing access to care across various medical fields, including prenatal care. While telehealth offers potential benefits such as improved healthcare access and reduced travel for pregnant women, its impact on psychosocial well-being and patient satisfaction during pregnancy remains insufficiently explored. This literature review aimed to explore the impact of telehealth on psychosocial well-being and patient satisfaction during pregnancy. Methods: This literature review employed the PICO method to develop the review question, focusing on randomized controlled trials published between 2020 and 2024, identified through SCOPUS, PubMed, and Google Scholar using specific keywords related to telehealth, pregnancy, and well-being. Result: Six relevant articles meeting the inclusion criteria. The review found that telehealth interventions during pregnancy improved psychosocial well-being by reducing stress and anxiety, enhancing social support, and increasing patient satisfaction compared to conventional prenatal care methods. Conclusion: The literature review concludes that telehealth may an effective approach to pregnancy care, providing accessible and continuous support through online consultations that overcome geographical challenges. The evidence suggests that telehealth enhances patient satisfaction and psychological well-being by offering a convenient, flexible, and personalized alternative to conventional in-person visits.